2017
DOI: 10.1093/toxsci/kfw256
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms involved in porcine early embryo survival following ethanol exposure

Abstract: Alcohol consumption during pregnancy is still a cause of preventable birth defects and developmental disabilities. However, little is known about the impact of ethanol on preimplantation embryos and the molecular mechanisms involved. We aimed to determine the toxicogenomic impacts and the mechanisms involved in preimplantation embryonic survival following 0.2% ethanol exposure in porcine embryos. Gene expression changes were measured with a porcine embryo specific microarray and confirmed by RT-qPCR. When comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Nevertheless, such studies along with others [ 67 ] confirm that even prior to direct maternal–fetal interface exchanges via the placenta, alcohol can reach the developing pre-implantation embryos through the female reproductive track. In vitro studies support that pre-implantation embryos are sensitive and negatively affected by alcohol exposure [ 68 ]. Although less investigated and understood than maternal exposure, studies suggest that alterations (e.g., epigenetic errors) initiated on the fathers' sperm are passed-on during fertilization to pre-implantation embryos, influence development beyond implantation, and lead to abnormal offspring development (e.g., fetal growth restriction, birth defects, placental defects) [ 58 , 69 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such studies along with others [ 67 ] confirm that even prior to direct maternal–fetal interface exchanges via the placenta, alcohol can reach the developing pre-implantation embryos through the female reproductive track. In vitro studies support that pre-implantation embryos are sensitive and negatively affected by alcohol exposure [ 68 ]. Although less investigated and understood than maternal exposure, studies suggest that alterations (e.g., epigenetic errors) initiated on the fathers' sperm are passed-on during fertilization to pre-implantation embryos, influence development beyond implantation, and lead to abnormal offspring development (e.g., fetal growth restriction, birth defects, placental defects) [ 58 , 69 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such studies along with others (Sandor, Gârban, Checiu, & Daradics, 1981) confirm that even prior to direct maternal-fetal interface exchanges via the placenta, alcohol can reach the developing pre-implantation embryos through the female reproductive track. In vitro studies support that pre-implantation embryos are sensitive and negatively affected by alcohol exposure (Pagé-Larivière, Campagna, & Sirard, 2017). It remains to be defined whether some of the milder abnormalities or delays that we observed at mid-gestation would become resolved or accentuated by birth, and whether embryos that presented no visible abnormalities or developmental delays but had DNA methylation alterations would show cognitive dysfunctions as observed in other FASD-models and children with FASD.…”
Section: Modeling Early Pre-implantation Alcohol Exposurementioning
confidence: 64%
“…Although pioneer work demonstrated that early embryonic alcohol exposure can negatively influence development (Checiu and Sandor, 1986;Fazakas-Todea et al, 1986;Wiebold and Becker, 1987;Padmanabhan and Hameed, 1988), we still don't fully understand how alcohol directly impacts the early embryo, especially its epigenome. A recent report shows that porcine zygotes exposed to alcohol in vitro have a lower rate of blastocyst formation, with blastocysts having increased mitochondrial dysfunctions and abnormal gene expression (Page-Lariviere et al, 2017). Haycock and Ramsay (2009) did show in a mouse model that alcohol exposure at E1.5 and E2.5 was associated with loss of H19 imprinted DNA methylation in the placenta at E10.5 and growth restriction (Haycock and Ramsay, 2009).…”
Section: Adverse Stressorsmentioning
confidence: 98%